Efektifitas Pelaksanaan Pencegahan Diabetes Mellitus Tipe II melalui Media Video Edukasi Senam Kaki Diabates di RS Balimed Denpasar - Prihandhani, I Gusti Agung Ayu Sherlyna; Trisna, Made Oktaviani Bulan; Widiastuti, Putu (Universitas Nusantara PGRI Kediri, 2025)
The increase in blood sugar levels accompanied by impaired carbohydrate, fat, and protein metabolism due to insulin deficiency is a sign of chronic metabolic disease or diabetes mellitus (DM). This disease has many causes and can last for years. Management of diabetes in hospitals, in addition to using pharmacological therapy, also applies non-pharmacological strategies. One of the non-pharmacological efforts is foot gymnastics. Foot gymnastics has benefits for various muscle and joint problems. The method in this community service uses the lecture method and demonstration of diabetes mellitus foot gymnastics. The results of this community service obtained an increase in the pre-test value which was previously an average of 51.5, increasing after being given a lecture and demonstration to 75.75 post-test value. It is hoped that in the future the elderly will be able to independently apply diabetes foot gymnastics to prevent foot wounds.